REPRESENTASI WOMEN EMPOWERMENT MELALUI KARAKTER PENARI STRIPTIS PEREMPUAN DALAM FILM HUSTLERS - Aqila Almas Aisyi; Triyono Lukmantoro; Muhammad Bayu Widagdo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Women's empowerment is a process whereby women who previously did not have the ability to make choices and decisions in life, eventually gain this ability. This film offers an alternative idea by conveying the message of feminism, namely women empowerment in the form of a female striptease dancer character who is brave, strong, and able to make decisions in life, amongst the dominant understanding of striptease dancers being looked down upon, ignored, and ostracized. This research aims to describe the depiction of the reality of the life of striptease dancers, dominant ideology, and the representation of women empowerment through the female striptease dancer characters featured in the Hustlers film. This research uses representation theory, standpoint theory, and performance theory, and uses John Fiske's semiotic analysis method, which will analyze at the reality, representation, and ideology level. The research resulting women have strategies to improve the economic situation by putting aside stereotypes of striptease dancers, their willingness to learn more, broaden skills, and raise public awareness about women's equality. New ideological findings were also found in the form of transformative gender equality, women’s participation, women’s democratization, women’s language, and women’s subordination in men’s opression.